Systematic Layout Planning Approach in Process Layout Design for Processing Dehydrated Tomatoes - Abdulhakeem, N. H.; Muhammad, I. D.; Dagwa, I. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
This study was conducted to determine an effective design for the processing of dehydrated tomatoes. The study proffer solutions to huge losses Nigeria encounters as a result of poor postharvest handling across the fruits and vegetables value chain. Despite the huge contributions of agriculture (vegetables) to Nigeria’s economic growth, postharvest losses stands at 9 million with 50% losses in fruits and vegetables as a result of their perishable nature. Systematic layout planning (SLP) approach was used in designing the process layout for dehydrated tomatoes. The design approach was used to serve as an improvement layout and also as a new design for processing of dehydrated tomato plant, with estimated 5% material losses during processing, average temperature for dehydration as 65oC, plant production time of 748.99 minutes/day, a throughput capacity of 10 tons/day is achievable. Additionally, the design was validated using computer simulation and the results obtained from the simulation analysis indicated that the method can be used to optimize process planning for several production processes of dehydrated fruit and vegetables.